2010
DOI: 10.2147/oajc.s12194
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Implanon® on antituberculous therapy

Abstract: Implanon ® , a contraceptive implant, is increasingly being used because of its efficacy and nonuser-dependent nature. However, as for other steroid contraceptives, its efficacy can be reduced by enzyme-inducing drugs, such as antituberculous medication, resulting in unplanned pregnancy. We present the case of a 27-year-old para 1 + 0 referred to us for termination of a pregnancy that resulted from failure of Implanon during concomitant treatment with Rifinah ® (a rifampicin-isoniazid combination). All health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Its main mechanism of action is ovulation suppression, augmented by increased cervical mucus viscosity that hinders the passage of spermatozoa and alters the endometrial lining [2, 4]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its main mechanism of action is ovulation suppression, augmented by increased cervical mucus viscosity that hinders the passage of spermatozoa and alters the endometrial lining [2, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…More than 4.5 million women have used Implanon worldwide [4, 6]. In sub-Saharan Africa, a growing number of women and sexually active adolescents are using family planning, and many are choosing contraceptive implants [7].…”
Section: Introductionmentioning
confidence: 99%
“…Common hepatic enzyme AED inducers include phenytoin, phenobarbital, oxcarbazepine, topiramate, and carbamazepine [19,21,22]. Nonnucleoside reverse transcriptase inhibitors (efavirenz) and antituberculosis medications (isoniazid) also have CYP induction properties [23,24]. These medications induce the CYP450 3A4 system to accelerate the metabolism of estrogen and progestin; thereby decreasing the available serum concentration of progestin [19,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this case series identified that a number of failures occurred as a result of concomitant use of enzyme inducing drugs (Harrison-Woolrych and Hill 2005). Other reports of failures possibly as a consequence of drug interactions are documented (Patni et al 2006;Lakhi and Govind 2010;McCarty et al 2011;Matiluko et al 2007;Haukkamaa 1986;Gbolade 2010): product information warns that efficacy may be reduced with concomitant use of drugs which induce hepatic enzymes, specifically cytochrome P450, for example carbamazepine or rifampacin (Merck Sharp and Dohme Limited 2013). In 2014, the Medicines and Healthcare Regulatory Agency (MHRA) in the UK produced a Drug Safety Update (Medicines and Healthcare Products Regulatory Agency 2014) which highlighted that in the last quarter of 2013 the MHRA had received two reports of unintended pregnancies occurring in women using the etonogestrel implant possibly as a consequence of using St John's Wort.…”
Section: Efficacy and Unintended Pregnanciesmentioning
confidence: 94%